Sustainable Neighborhood in the Kemayoran Sunter Area - Sapto Nugroho; Metta Vimalla Shanti; Dedes Nurgandarum (Journal of Social Research, 2026)
The KemayoranSunter area represents the urban transformation in Jakarta, from airport land and industrial landfill to a modern mixeduse center that includes offices, residential, and commercial, but this evolution actually poses complex challenges in achieving sustainable neighborhood status. The study highlights a review of eight dominant dimensions that are the main bottlenecks: water and climate biodiversity, carbon footprints, spatial design, renewable energy, landscape resilience, social justice, and environmental risks. This literature review uses a review approach of scientific journals and other documents to identify the dominant factors of inhibitions, such as post-industrial environmental degradation and socioeconomic imbalances, which are systematically analyzed through the eight-dimensional framework. The goal is to produce a comprehensive evaluation framework, allowing the measurement of the region's performance against global sustainable neighborhood standards while compiling contextual regenerative recommendations. This framework and recommendations are intended for stakeholders including local governments, property developers, and communities as a basis for development considerations, with a focus on holistic transformation towards a healthy, inclusive, and resilient environment, so that the KemayoranSunter Area can become an adaptive urban model in Indonesia